NEEDS AND SOURCES OF INFORMATION ON DISEASE MANAGEMENT FOR PARENTS OF CHILDREN WITH DIABETES MELLITUS - Čergelytė - Podgrušienė, Indrė; Gudžinskienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Type 1 diabetes mellitus in children alters the rhythm and daily routines of children and parents, as there appears a need to treat and control this disease. Parents need to learn how to optimally care for the health of their children: monitor levels of blood glucose, follow a diet plan, inject insulin and organize the child’s schedule. Research object: needs and sources of information for parents of children with diabetes mellitus on the management of their child’s disease. Research aim is to reveal the needs and sources of information on the disease and its management for parents of children with diabetes mellitus. Research tasks: 1) to identify the needs of parents of children with diabetes mellitus for information on the disease management; 2) to reveal how and in what ways parents search for information on the child’s disease and its management. Research methods: theoretical – analysis, generalization and systematization of scientific literature; empirical – a semi-structured method of interview has been used for the collection of data; method of content analysis has been applied to the study of research data. There were 6 women of children with diabetes mellitus, who agreed to participate in the research. Participants of the research raise children who have diabetes mellitus up to 3 years after diagnosis; children’s age ranges from 3 to 11 years old. All women had higher education. The empirical study revealed that mothers of children with diabetes mellitus require information on the child’s disease and its control. Participants of the research mentioned that they try to obtain information from various sources: medical institutions, relatives, the Internet, social networks, etc.